Students’ Knowledge of HIV/AIDS and their Attitude towards Sexual Behaviour- A Comparative study of Form 1 and Form 4 secondary school students in Coast Region, Kenya - Dr Daniel Njane Thuo, Dr Barchok H. K, Prof. Veronica N., Dr Bururia D. (International Journal of Emerging Trends in Science and Technology, 2018)
National AIDS Control Council and the Ministry of Education Science and Technology in Kenya developed the 2004 Education Sector Policy on HIV and AIDS. The policy was intended to reduce HIV/AIDS infection and stigmatisation of people living with HIV in the education sector. However, it is not known how implementation of the policy has affected students’ knowledge and their attitude towards sexual behaviour in secondary schools in Coast Region of Kenya. The research study investigated the students’ knowledge of HIV/AIDS and their attitude towards sexual behaviour in secondary schools in coast region of Kenya. The target population was 108693 respondents in 362 public secondary schools in the Coast Region of Kenya. Purposive and random sampling methods were used to choose the participants. The samples comprised of 388 students of which 193 were Form 1 and 195 were Form 4 students in 13 secondary schools. The validity of the questionnaires was checked experts at Chuka University. Test-retest method was used to compute reliability coefficient from the data collected from the pilot study. Reliability coefficient for the instruments was 0.8. The descriptive statistics used were frequencies and percentage. Chi-squire statistics was used to test the hypotheses in the study. The hypotheses testing were done at α = 0.05 levels of significance and the analyses was done using SPSS computer programme version 20.0. The findings showed that there was a positive relationship between Form 1 and Form 4 students’ knowledge of HIV/AIDS in secondary schools in Coast Region of Kenya. The study also revealed that there was negative relationship between Form 1 and Form 4 students’ attitude towards sexual behaviour. It was recommended that secondary schools should enhance the teaching of HIV/AIDSin order to reduce HIV infection AIDS among secondary students in Coast region, Kenya.